Onco-immunomodulatory properties of pharmacological interference with RAS-RAF-MEK-ERK pathway hyperactivation - Avery, Thomas Yul; Köhler, Natalie; Zeiser, Robert; Brummer, Tilman; Ruess, Dietrich Alexander (Frontiers in Oncology, 2022)
Hyperactivation of the RAS-RAF-MEK-ERK cascade - a mitogen-activated protein kinase pathway – has a well-known association with oncogenesis of leading tumor entities, including non-small cell lung cancer, colorectal carcinoma, pancreatic ductal adenocarcinoma, and malignant melanoma. Increasing evidence shows that genetic alterations leading to RAS-RAF-MEK-ERK pathway hyperactivation mediate contact- and soluble-dependent crosstalk between tumor, tumor microenvironment (TME) and the immune system resulting in immune escape mechanisms and establishment of a tumor-sustaining environment. Consequently, pharmacological interruption of this pathway not only leads to tumor-cell intrinsic disruptive effects but also modification of the TME and anti-tumor immunomodulation. At the same time, the importance of ERK signaling in immune cell physiology and potentiation of anti-tumor immune responses through ERK signaling inhibition within immune cell subsets has received growing appreciation. Specifically, a strong case was made for targeted MEK inhibition due to promising associated immune cell intrinsic modulatory effects. However, the successful transition of therapeutic agents interrupting RAS-RAF-MEK-ERK hyperactivation is still being hampered by significant limitations regarding durable efficacy, therapy resistance and toxicity. We here collate and summarize the multifaceted role of RAS-RAF-MEK-ERK signaling in physiology and oncoimmunology and outline the rationale and concepts for exploitation of immunomodulatory properties of RAS-RAF-MEK-ERK inhibition while accentuating the role of MEK inhibition in combinatorial and intermittent anticancer therapy. Furthermore, we point out the extensive scientific efforts dedicated to overcoming the challenges encountered during the clinical transition of various therapeutic agents in the search for the most effective and safe patient- and tumor-tailored treatment approach.